Numerical and spatial patterning of yeast meiotic DNA breaks by Tel1 - Mohibullah, Neeman; Keeney, Scott (Genome Research, 2017)
The Spo11-generated double-strand breaks (DSBs) that initiate meiotic recombination are dangerous lesions that can disrupt genome integrity, so meiotic cells regulate their number, timing, and distribution. Mechanisms of this regulation remain poorly understood. Here, we use Spo11-oligonucleotide complexes, a byproduct of DSB formation, to reveal aspects of the contribution of the Saccharomyces cerevisiae DNA damage-responsive kinase Tel1 (ortholog of mammalian ATM). A tel1Δ mutant has globally increased amounts of Spo11-oligonucleotide complexes and altered Spo11-oligonucleotide lengths, consistent with conserved roles for Tel1 in control of DSB number and processing. A kinase-dead tel1 mutation similarly increases Spo11-oligonucleotide levels but mutating known Tel1 phosphotargets on Hop1 and Rec114 does not, implicating Tel1 kinase activity and clarifying roles of Tel1 phosphorylation substrates. Deep sequencing of Spo11 oligonucleotides demonstrates that Tel1 shapes the genome-wide DSB landscape in unexpected ways. Early in meiosis, Tel1 absence causes widespread changes in DSB distributions across large chromosomal domains. Many of these changes are erased as meiosis proceeds, however, illustrating homeostatic behavior of DSB regulatory systems. We further find that effects of Tel1 are distinct but partially overlapping with previously described contributions of the recombination regulator Cst9 (also known as Zip3). Finally, we provide evidence indicating that Tel1-dependent DSB interference influences the population-average DSB landscape but also demonstrate that locally inhibitory effects of an artificial hotspot insertion can be both Tel1-independent and chromosomal context-dependent. Our findings delineate Tel1 roles in regulating number and location of DSBs and illuminate the complex interplay between Tel1 and other pathways for DSB control.
10.1101/gr.213587.116